The Integrator complex desensitizes cellular response to TGF-?/BMP signaling. - Liu, S.; Baeg, G.H.; Yang, Y.; Goh, F.G.; Bao, H.; Wagner, E.J.; Yang, X.; Cai, Y. (Cell reports, 2023)
Maintenance of stem cells requires the concerted actions of niche-derived signals and stem cell-intrinsic factors. Although Decapentaplegic (Dpp), a Drosophila bone morphogenetic protein (BMP) molecule, can act as a long-range morphogen, its function is spatially limited to the germline stem cell niche in the germarium. We show here that Integrator, a complex known to be involved in RNA polymerase II (RNAPII)-mediated transcriptional regulation in the nucleus, promotes germline differentiation by restricting niche-derived Dpp/BMP activity in the cytoplasm. Further results show that Integrator works in various developmental contexts to desensitize the cellular response to Dpp/BMP signaling during Drosophila development. Mechanistically, our results show that Integrator forms a multi-subunit complex with the type I receptor Thickveins (Tkv) and other Dpp/BMP signaling components and acts in a negative feedback loop to promote Tkv turnover independent of its transcriptional activity. Similarly, human Integrator subunits bind transforming growth factor ? (TGF-?)/BMP signaling components and antagonize their activity, suggesting a conserved role of Integrator across metazoans.